2003
DOI: 10.1080/0880010390158487
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Transfusion Regimens in the Perioperative Management of Children with Sickle Cell Disease Undergoing Adenotonsillectomy

Abstract: Adenotonsillar hypertrophy and chronic tonsillitis are common findings in patients with sickle cell disease (SCD). Various preoperative transfusion regimens have been suggested to reduce the population of sickle erythrocytes and correct the anemia, ranging from conservative (correcting the anemia) to aggressive (lowering the level of HbS to less than 30%). A total of 39 patients with SCD were included in the study. They were divided into 2 groups. Fourteen patients in group 1 were assigned aggressive exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Excessive adenoidal and tonsillar growth occurs in children with SCD secondary to lymphoid tissue hyperplasia or recurrent tonsillitis 65 . Adenotonsillar hypertrophy is a risk factor for obstructive sleep apnea and vaso-occlusive crisis due to periods of hypoxemia 66 . Sleep patterns in children with SCD have not been well characterized, although studies report associations among nocturnal hypoxemia, SDB, and sleep disruption secondary to pain 46,6769 .…”
Section: Medical Conditions Associated With Sleep Problemsmentioning
confidence: 99%
“…Excessive adenoidal and tonsillar growth occurs in children with SCD secondary to lymphoid tissue hyperplasia or recurrent tonsillitis 65 . Adenotonsillar hypertrophy is a risk factor for obstructive sleep apnea and vaso-occlusive crisis due to periods of hypoxemia 66 . Sleep patterns in children with SCD have not been well characterized, although studies report associations among nocturnal hypoxemia, SDB, and sleep disruption secondary to pain 46,6769 .…”
Section: Medical Conditions Associated With Sleep Problemsmentioning
confidence: 99%
“…The role for antibioprophylaxis is discussed by many, and two strategies seem to co‐exist in the literature. There are authors recommending prophylaxis according to type of surgery, and others adapting it to the individual patients' medical histories . As a standout, splenectomy needs specific considerations, including preoperative immunizations against encapsulated bacteria, as in the context of asplenia .…”
Section: Resultsmentioning
confidence: 99%
“…Thrombophilia evaluation is suggested, in some reviews . Preoperative preparation occasionally includes chest physiotherapy and intra‐venous hydration during the fasting period . Bicarbonate treatment, as a prevention to acidosis, has been reported as a standard treatment in older manuscripts .…”
Section: Resultsmentioning
confidence: 99%
“…1 Patients with SCD commonly have adenotonsillar hypertrophy and chronic tonsillitis, with a prevalence ranging from 25 to 55%. 2,3 Though the causes of adenotonsillar hypertrophy are still unclear, numerous mechanisms are proposed such as compensatory hypertrophy of the lymphoid tissue for functional asplenia, reactive enlargement due to repeated infections and increased hematopoietic needs because of chronic hemolytic anemia. 4,5 Adenotonsillar hypertrophy can increase the risk of obstructive sleep apnea, hypoxemia, dehydration, and predisposes to several complications in patients with SCD including vaso-occlusive crisis (VOC), pulmonary hypertension, acute chest syndrome (ACS), priapism or even stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have demonstrated that simple transfusion is as effective as exchange transfusion in reducing postoperative complications in patients with SCD and it requires much less blood volume. 2,7,9,10 The aim of the current work is to compare between simple packed red cell (PRBCs) transfusion and non-transfusion policy as a preoperative management strategy in stable pediatric patients with SCD undergoing adenotonsillectomy and to study the risks and benefits of both approaches.…”
Section: Discussionmentioning
confidence: 99%